Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Airflow Simulations in Infant, Child, and Adult Pulmonary Conducting Airways - Jessica M. Oakes; Steven C. Roth; Shawn C. Shadden (Annals of Biomedical Engineering, 2018)

Protein Kinase B (Akt) and Mitogen-Activated Protein Kinase p38α in Retinal Ischemic Post-Conditioning - John C. Dreixler; Ajay Sampat; Afzhal R. Shaikh; Michael Alexander; Marcus M. Marcet; Steven Roth (Journal of Molecular Neuroscience, 2011)

Generation of Priority Research Questions to Inform Conservation Policy and Management at a National Level - MURRAY A. RUDD; KAREN F. BEAZLEY; STEVEN J. COOKE; ERICA FLEISHMAN; DANIEL E. LANE; MICHAEL B. MASCIA; ROBIN ROTH; GARY TABOR; JISELLE A. BAKKER; TERESA BELLEFONTAINE; DOMINIQUE BERTEAUX; BERNARD CANTIN; et al. (Conservation Biology, 2011)
Integrating knowledge from across the natural and social sciences is necessary to effectively address societal tradeoffs between human use of biological diversity and its preservation. Collaborative processes can change the ways decision makers think about scientific evidence, enhance levels of mutual trust and credibility, and advance the conservation policy discourse. Canada has responsibility for a large fraction of some major ecosystems, such as boreal forests, Arctic tundra, wetlands, and temperate and Arctic oceans. Stressors to biological diversity within these ecosystems arise from activities of the country's resource‐based economy, as well as external drivers of environmental change. Effective management is complicated by incongruence between ecological and political boundaries and conflicting perspectives on social and economic goals. Many knowledge gaps about stressors and their management might be reduced through targeted, timely research. We identify 40 questions that, if addressed or answered, would advance research that has a high probability of supporting development of effective policies and management strategies for species, ecosystems, and ecological processes in Canada. A total of 396 candidate questions drawn from natural and social science disciplines were contributed by individuals with diverse organizational affiliations. These were collaboratively winnowed to 40 by our team of collaborators. The questions emphasize understanding ecosystems, the effects and mitigation of climate change, coordinating governance and management efforts across multiple jurisdictions, and examining relations between conservation policy and the social and economic well‐being of Aboriginal peoples. The questions we identified provide potential links between evidence from the conservation sciences and formulation of policies for conservation and resource management. Our collaborative process of communication and engagement between scientists and decision makers for generating and prioritizing research questions at a national level could be a model for similar efforts beyond Canada.

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

The predatory behavior of wintering Accipiter hawks: temporal patterns in activity of predators and prey - Timothy C. Roth; Steven L. Lima (Oecologia, 2007)

Determinants of predation risk in small wintering birds: the hawk’s perspective - Timothy C. Roth; Steven L. Lima; William E. Vetter (Behavioral Ecology and Sociobiology, 2006)

Polymorphic variation of CYP1A1 is associated with the risk of gastric cardia cancer: a prospective case?cohort study of cytochrome P-450 1A1 and GST enzymes - Mark J. Roth; Christian C. Abnet; Laura Lee Johnson; Steven D. Mark; Zhi Wei Dong; Philip R. Taylor; Sanford M. Dawsey; You-Lin Qiao (Cancer Causes & Control, 2004)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)